1983
DOI: 10.1159/000149391
|View full text |Cite
|
Sign up to set email alerts
|

Follow-Up Studies on Epstein – Barr virus IgA/VCA Antibody-Positive Persons in Zangwu County, China

Abstract: Serological mass surveys were carried out in Zangwu County, China, using an immunoenzymatic test. 3,533 persons were found to have Epstein-Barr virus (EBV) IgA/VCA antibody among 148,029 persons age 30 years and older who were tested during 1978–1980. Among the IgA/VCA antibody-positive persons, 55 nasopharyngeal carcinoma (NPC) cases were detected. Follow-up studies were carried out yearly on the IgA/VCA antibody-positive persons for 1–3 years, and 32 additional NPC patients were diagnosed. IgA/VCA antibody w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
47
0

Year Published

1997
1997
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(55 citation statements)
references
References 3 publications
(3 reference statements)
5
47
0
Order By: Relevance
“…The overall prediction rate (56/131) achieved by serologic screening conducted at the time of enrollment is similar to that reported by Chien et al (2001), but lower than that achieved by Yi et al (1980) and Zeng et al (1983). The cumulative incidence of the entire study population calculated over 15 years is 21 per 10 5 person-year.…”
Section: Resultssupporting
confidence: 64%
See 1 more Smart Citation
“…The overall prediction rate (56/131) achieved by serologic screening conducted at the time of enrollment is similar to that reported by Chien et al (2001), but lower than that achieved by Yi et al (1980) and Zeng et al (1983). The cumulative incidence of the entire study population calculated over 15 years is 21 per 10 5 person-year.…”
Section: Resultssupporting
confidence: 64%
“…It has a strong association with the human herpesvirus, Epstein -Barr virus (EBV) (Raab-Traub, 2002), with general elevation of serum EBV antibody level being an outstanding feature of the tumour (Olds et al, 1966;Henle et al, 1970;Henle and Henle, 1976;Ho et al, 1978a;Zeng et al, 1983;Cheng et al, 2002;Chan et al, 2003;Fachiroh et al, 2004). EBV antibody screening in sera of populations in high incidence areas for NPC can be useful in predicting onset of the cancer (Yi et al, 1980;Zeng et al, 1983;Chien et al, 2001;Ji et al, 2003a, b). This is presumed to reflect rises in antibody levels at an early stage in cancer development (Ho et al, 1978a;Cheng et al, 2002).…”
mentioning
confidence: 99%
“…1 Although several previous studies [2][3][4][5] have reported on the use of EBV serology for screening and early detection of NPC, the role of EBV DNA detection as a screening test for NPC remains to be defined. Circulating cell-free EBV DNA is detectable in the plasma of 96% of NPC patients 6 by quantitative real-time polymerase chain reaction (PCR) and has been shown to be a useful marker in prognostication 7 as well as residual disease detection.…”
Section: Dear Sirmentioning
confidence: 99%
“…Although several prior studies (Zeng et al, 1982;Zeng et al, 1983;Zeng et al, 1985;Tsang et al, 2004) have demonstrated on the use of EBV serology for screening and early detection of NPC, the role of EBV DNA detection as a screening test for NPC remains inconclusive. Previous research has reported that cell-free EBV DNA can be quantitatively measured in the blood of NPC patients using polymerase chain reaction (PCR) technique Shotelersuk et al, 2000;Lin et al, 2001;Chan et al, 2003;Fan et al, 2004).…”
Section: Introductionmentioning
confidence: 99%